Zmote o usvajanju funkcionalne pismenosti v e-okolju in nove naloge didaktike slovenščine - Kordigel Aberšek, Metka (Slavia Centralis, 2020)
MISCONCEPTIONS ABOUT FUNCTIONAL LITERACY ACQUISITION IN E-ENVIRONMENTS AND THE NEW TASKS OF SLOVENIAN LANGUAGE DIDACTICS Over the past decade, reflections on mother tongue curricula in 21st century schools have often stemmed from certain misconceptions about Generation Z. Digital natives, as members of Gen Z are often called, supposedly do not need linear reading skills anymore; the keyboard is supposedly replacing the pen entirely, and, most dangerously, the children of today are supposed to develop their functional literacy in e-environments automatically, which is why they do not require to be taught this at school. Relevant theoretical findings and empirical research, however, show that all these three beliefs are erroneous and that they should not influence the design of new mother tongue curricula.